In situ observation of plaster microstructure evolution during thermal loading. (November 2016) - Payraudeau ‐ Le Roux, N.; Meille, S.; Chevalier, J.; Maire, E.; Adrien, J.
SUMMARY: Gypsum microstructural evolution at elevated temperatures has been characterized in situ by environmental scanning electron microscopy and high‐temperature X‐ray tomography. As temperature increases, the observed changes in gypsum crystal morphology are related to the consequences of water loss that leads to crystal reorganization in order to minimize the specific surface. The influence of environmental scanning electron microscopy experimental conditions on the mechanisms observed is also discussed. High‐temperature X‐ray tomography gives quantitative information on porosity evolution with thermal loading. The results obtained are successfully correlated with macroscopic shrinkage measurements performed during dilatometry tests. Copyright © 2016 John Wiley & Sons, Ltd.